Biological aspects and ecological effects of a bed of the invasive non-indigenous mussel Brachidontes pharaonis (Fischer P., 1870) in Malta - BONNICI, L.; EVANS, J.; BORG, J.A.; SCHEMBRI, P.J. J. (Mediterranean Marine Science, 2012)
No mussel beds were known to occur in the Maltese Islands previous to 2009, when a single bed of the Lessepsian immigrant Brachidontes pharaonis, first recorded from the islands in 1970, was discovered in Birzebbugia Bay. The population structure of B. pharaonis was investigated to assess its potential to spread and colonise new shores, while the biotic community at the mussel bed was compared to that present on uncolonised substratum to determine the effects of mussel bed establishment on the associated biota. Results indicate a lower species richness and slightly different community structure with greater small-scale heterogeneity at the mussel bed site compared to the adjacent rocky shore where mussels are present but where there is no bed formation. The B. pharaonis population had a peak density of 16550 ± 2051 ind.m-2 within the mussel bed and included recent recruits. These data suggest that the B. pharaonis population has the potential to expand. Establishment of extensive beds by this invasive mussel could change the structure of native rocky shore assemblages around the Maltese Islands and elsewhere in the Mediterranean.